Integrated fly management for control of house fly (Diptera: Musca domestica) in layer chicken farms: A review - PONNUDURAI, G; RANI, N; VELUSAMY, R (The Indian Journal of Animal Sciences, 2015)
The house fly, a major arthropod pest, causes great annoyance to birds, farm labourers and public residing in the vicinity of farms. The problem of house menace at times reaches beyond threshold level in poultry farms, particularly, in caged layer farms, leading to public health issue. Control of this challenging pest largely relies on various classes of insecticides. Realizing the inherent limitations with insecticide application over the years, much emphasize is being given for fly control through integrated fly management in the recent times. Hence, social and public health problems associated with house fly population, and various modules of integrated fly management such as biology of flies, factors responsible for fly problem, fly monitoring, litter management; farm sanitations, insect growth regulators, insecticide application, plant derivatives, entomopathogenic fungi and entomopathogenic nematode, bacterial pathogens, parasitoids and predators are discussed in this review.